A Curriculum on Sustainable Information Communication Technology - Özkan, Barış; Mishra, Alok (Problemy Ekorozwoju, 2015)
Economies are increasingly becoming dependent on Information Communication Technology (ICT) and concerns over sustainability have called for the investigation of the relation between sustainability and ICT. While the majority of the studies in this field have an environmentalist focus in this regard, technical, economical and societal concerns on sustainability have arisen in the last decade. Today, more and more studies are addressing the need for the inclusion of sustainability as a design goal for ICT development and for the systems that rely on ICT. Therefore, the integration of education on sustainability in the curriculum is imperative for current and future generations of professionals to accomplish this goal. In this paper, we propose a curriculum for sustainable ICT along with the expected learning outcomes and components. The course design is based on a multi-faceted approach that embraces different viewpoints on sustainability and aims to increase students’ awareness of the complex nature of sustainability.